(untitled) (Journal of Parents and Teachers, 1995)
Children’s education is influenced by family and environmental factors, where parental figures play a crucial role in their development. It is essential for parents to recognize their mistakes and communicate effectively in order to transmit positive values. Awareness of their own limitations and willingness to change are essential for successful parenting.